Molecular characterization of the interaction of Borrelia parkeri and Borrelia turicatae with human complement regulators - Schott, Melanie; Grosskinsky, Sonja; Brenner, Christiane; Kraiczy, Peter; Wallich, Reinhard (Infection and immunity, 2010)
In North America, tick-borne relapsing fever is caused by the species Borrelia hermsii, B. parkeri, and B. turicatae, which are transmitted to humans through the bite of the respective infected tick vectors. Here we describe the identification and functional characterization of a surface lipoprotein of B. parkeri, designated BpcA, that binds the human complement regulators factor H and factor H-related protein 1 and, simultaneously, the host protease plasminogen. In contrast, the homologous B. turicatae protein failed to bind human factor H and factor H-related protein 1 but retained its plasminogen binding capacity. Factor H bound to BpcA maintains its regulatory capacity to control C3b deposition and C3 convertase activity. Ectopic expression of BpcA in a serum-sensitive B. burgdorferi strain protects transformed cells from complement-mediated killing. Furthermore, bound plasminogen/plasmin endows B. parkeri and B. turicatae with the potential to degrade extracellular matrix components. These findings expand our understanding of the putative recent evolutionary separation of Borrelia parkeri and Borrelia turicatae, provide evidence that B. parkeri differs from B. turicatae in its ability to resist complement attack, and may help in understanding the pathological processes underlying tick-borne relapsing fever.
Gesehen am 17.05.2021